Mushaf Al-Qur'an Kuno di Priangan Kajian Rasm, Tanda Ayat, dan Tanda Waqaf - Syatri, Jonni (Lajnah Pentashihan Mushaf Al-Qur'an, 2013)
This paper examines the ancient manuscripts of the Qur'an available in Priangan island, especially in Bandung, Sumedang, and Garut. The aspects being studied are that of the form and style of the writings (Rasm), the sign of the verse (Surah) and the sign of the stopping (waqaf). The aim of this paper is to observe the comparison among those manuscripts (Mushaf) which are spread across the three regions concerning the use of the form and style of the writings (Rasm) in copying the manuscripts of the Qur'an, whether it follows the form and style of the writings (Rasm) of the Ã¢â‚¬ËœUsmÃ„ÂnÃ„Â« or follows that of the ImlÃ„Â'i one. Besides that is to observe the variety of the use of the verse (Surah) and that of the stopping signs (waqaf) verse in those manuscripts. Keywords: Priangan, ancient Qur'anic manuscripts, Form and style of the writings (Rasm), the sign of the verse, waqaf.